Trade Credit Supply: An Empirical Investigation of Companies Level Data - Salima Paul; Nick Wilson (Journal of Accounting, Business and Management (JABM), 2006)
Trade credit is an important economic phenomenon and a variety of theories have been put forward to explain the decision firms make on credit extension. This paper reports an empirical investigation of a number of aspects of trade credit supply decisions which aims to test these theories using a rich level dataset from a survey of 355 UK companies. Multivariate models of trade credit supply are developed to explore aspects of the characteristics that drive trade credit extension decisions. Our results suggest that trade credit supply is a set of subtle and complex motivations over and above those predicted by standard theory. In particular, trade credit extension can be used as a many-faced marketing/relationship management tool and/or as a means of signalling information to the market or to specific buyers about the firm, its products and future prospects/commitment. Much of credit extension can be seen as customer focused, encouraging frequent purchasers which offer the potential for relationship development, for example, or accommodating customers demand for credit to help finance their production period. The requirements/bargaining power of large customers can influence a firm to extend more credit. Firms will vary terms in anticipation of capturing new business, to attract specific customers and in order to achieve specific marketing aims.